2012
DOI: 10.1242/jeb.065094
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function in sparrow pectoralis muscle

Abstract: SUMMARYFlying birds couple a high daily energy turnover with double-digit millimolar blood glucose concentrations and insulin resistance. Unlike mammalian muscle, flight muscle predominantly relies on lipid oxidation during locomotion at high fractions of aerobic capacity, and birds outlive mammals of similar body mass by a factor of three or more. Despite these intriguing functional differences, few data are available comparing fuel oxidation and free radical production in avian and mammalian skeletal muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 110 publications
5
21
0
Order By: Relevance
“…Importantly, the V max values reported in Table 2, determined using Eadie-Hofstee analysis of steady state conditions established with the creatine kinase energy clamp, are in excellent agreement with state 3 rates determined conventionally with saturating addition of ADP as seen in supplementary material Fig. S1, and also as recently reported by our laboratory (Kuzmiak et al, 2012).…”
Section: Kinetic Assessment Of Respiratory Control Sensitivitysupporting
confidence: 86%
See 3 more Smart Citations
“…Importantly, the V max values reported in Table 2, determined using Eadie-Hofstee analysis of steady state conditions established with the creatine kinase energy clamp, are in excellent agreement with state 3 rates determined conventionally with saturating addition of ADP as seen in supplementary material Fig. S1, and also as recently reported by our laboratory (Kuzmiak et al, 2012).…”
Section: Kinetic Assessment Of Respiratory Control Sensitivitysupporting
confidence: 86%
“…The state 3 (maximum) rate of mitochondrial oxygen consumption, J O , of pigeon pectoralis mitochondria oxidizing pyruvate is roughly equal to that of palmitoyl-L-carnitine (Rasmussen et al, 2004), and the pioneering work of Suarez et al showed similar trends in hummingbird pectoralis (Suarez et al, 1986). Data from pectoralis mitochondria of the house sparrow further confirm this avian pattern, as recently reported by our laboratory (Kuzmiak et al, 2012). As pyruvate (carbohydrate) and β-oxidation (fatty acid) pathways elicit equal rates of oxygen consumption, the selection of fatty acid fuel during avian flight cannot be simply explained by a higher catalytic potential for fat oxidation.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, the cell membranes of birds are composed of fatty acids that are more resistant to lipid peroxidation than those of mammals, and birds show lower overall lipid peroxidation rates in tissues (Hulbert and Else, 1999;Hulbert et al, 2007). Most mammals primarily use carbohydrates as fuel during exercise, whereas birds primarily burn fats to fuel flight, and this reliance on fatty acid oxidation results in relatively lower RS production in exercising birds than in mammals (Kuzmiak et al, 2012;Montgomery et al, 2012;Weber, 2009). Although burning fat may result in lower RS production in muscle mitochondria, stored fat is highly susceptible to lipid peroxidation, and, during migration, birds must build and store large amounts of fat (Costantini, 2014;Costantini et al, 2007;Pierce and McWilliams, 2014;Skrip et al, 2015).…”
Section: Among-species Differences In Bmrmentioning
confidence: 99%